Case report: Evaluation of cutaneous squamous cell carcinoma metastasized to lymph nodes using 18F-fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography in a dog - Seok, Jin; Lee, Sungin (Frontiers in Veterinary Science, 2024)
Introduction: 18F-fluorodeoxy-2-deoxy-D-glucose (FDG) positron emission tomography (PET) is used with high sensitivity in human medicine for initial staging and treatment planning of cutaneous squamous cell carcinoma (SCC). To the best of our knowledge, 18F-FDG PET/computed tomography (CT) has not been used for canine cutaneous SCC with lymph node metastasis.Case presentation: A 13 year-old spayed female Maltese had rapidly growing flank SCC, which had previously recurred twice. Radiography revealed no metastases. On PET/CT imaging, increased FDG uptake was observed not only in the flank but also in the left axillary lymph node and left inguinal lymph node (standardized uptake value max [SUVmax]: 8.602, 5.354, and 1.96, respectively). Despite the evidence of metastasis, palliative skin mass resection with a 3-cm margin and lymph node dissection were performed. Histopathological examination confirmed the presence of metastases in both lymph nodes.Discussion: 18F-FDG PET/CT is valuable for the detection of metastatic tumors in various organs. Cutaneous SCC can accumulate 18F-FDG, making it detectable on PET/CT. In this dog with flank SCC, 18F-FDG-PET/CT showed high SUVmax values, indicating its potential for tumor assessment. In veterinary medicine, SUVmax values of 2.5-3.5 are commonly used to identify metastatic lymph nodes in other cancers. Therefore, the interpretation of an SUVmax of 1.96 in an inguinal lymph node for metastatic involvement may be uncertain. Owing to the partial volume effect, 18F-FDG PET/CT has limited sensitivity in identifying LN metastases, particularly in cases of small lesions. Lower SUVmax values adjusted for smaller sizes may better distinguish between benign and malignant lymph nodes. Hence, combining differentiated SUVmax cut-offs based on lymph node size with CT assessment could enhance lymph node evaluation and assist in surgical planning.